ANALISA KINERJA MESIN PRESS SAMPAH PLASTIK BERDASARKAN LAMA WAKTU PRESS - Fadzal Taqwa Zafali; Anis Siti Nurrohkayati (JTM : JURNAL TEKNIK MESIN, 2026)
The abstract is to be in fully-justified italicized text, at the top of the paper with single column as it is here, below Plastic waste is a type of inorganic material that is difficult to decompose and can cause environmental pollution if not properly managed. One effective solution is compaction using a pressing machine to reduce waste volume, thereby facilitating transportation, storage, and recycling processes. This study aims to analyze the performance of a plastic waste pressing machine based on variations in pressing time to determine the optimal duration and compaction efficiency. The research method used is a quantitative experimental approach. A sample of 1 kg of used plastic bottles was processed using an automatic vertical pressing machine. The experiment was conducted four times with variations in pressing time ranging from 2.49 to 3.14 minutes. The observed parameters included initial and final height, compaction efficiency, height reduction, and compaction rate (cm/s). The results showed that compaction efficiency ranged from 72.73% to 75.90%, with an average of 74.32%. The pressing time of 2.49 minutes produced the highest efficiency, while the fastest compaction rate of 0.205 cm/s was observed in the first trial. The variation in pressing time was proven to affect both efficiency and machine performance, although not always proportionally. It can be concluded that the optimal pressing time ranges from 2.5 to 3.1 minutes. This study can serve as a basis for developing more efficient pressing machines for plastic waste management.